2010
DOI: 10.1016/j.stem.2010.02.016
|View full text |Cite
|
Sign up to set email alerts
|

HOW Is Required for Stem Cell Maintenance in the Drosophila Testis and for the Onset of Transit-Amplifying Divisions

Abstract: The mechanisms by which germline stem cells (GSCs) in the Drosophila testis undergo asymmetric division to regenerate a stem cell as well as a daughter (gonialblast) that will only undergo a further four mitotic divisions prior to entering premeiotic S phase and differentiating into a cyst of spermatocytes are not fully resolved. Here we demonstrate that the HOW RNA-binding protein is required for maintenance of CycB and therefore mitotic progression in GSCs and gonialblasts as well as determining the timing o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 35 publications
(46 reference statements)
8
50
0
Order By: Relevance
“…Taking into account the conserved nature of DDX3 proteins in eukaryotes, Kotov and coworkers (34) demonstrate that Belle is required cell-autonomously for mitotic progression and survival of GSCs and spermatogonia as the upstream regulator of mitotic cyclin expression. These results obtained using (44) (34,45,46) the Drosophila model support the importance of the tight regulation of mitotic cyclins in the fate determination of early germ cells. Both papers discussed here provide a significant insight into the functions of DDX3Y in spermatogenesis, suggesting that DDX3Y must be considered as en essential contributor to early male germ cell development and maintenance.…”
Section: Discussionsupporting
confidence: 65%
“…Taking into account the conserved nature of DDX3 proteins in eukaryotes, Kotov and coworkers (34) demonstrate that Belle is required cell-autonomously for mitotic progression and survival of GSCs and spermatogonia as the upstream regulator of mitotic cyclin expression. These results obtained using (44) (34,45,46) the Drosophila model support the importance of the tight regulation of mitotic cyclins in the fate determination of early germ cells. Both papers discussed here provide a significant insight into the functions of DDX3Y in spermatogenesis, suggesting that DDX3Y must be considered as en essential contributor to early male germ cell development and maintenance.…”
Section: Discussionsupporting
confidence: 65%
“…The modifier how encodes an RNA binding protein that can bind to dpp mRNA (Israeli et al 2007). How plays roles in integrin-mediated cell adhesion (Walsh and Brown 1998) and in the maintenance of stem-cell proliferation in testes (Monk et al 2010). Vps28 is a component of the ESCRT-I complex, which is required for trafficking of ubiquitylated proteins (Vaccari et al 2009) and has been shown to play a role in autophagy (Rusten et al 2007).…”
Section: Other Genetic Modifiersmentioning
confidence: 99%
“…We favor the first possibility for the following reasons. First, other cell cycle regulators, such as Cyclins A, B and E, do not show stem cell-specific high-level expression (Lilly et al, 2000;Boyle et al, 2007;Monk et al, 2010), implying that these cell cycle regulators are equally important in stem cell compartments and transit-amplifying cells. Second, overexpression of Cdc2 (Cdk1) or Cdk4 together with Cyclin D (Meyer et al, 2002) did not lead to overproliferation of the CySCs (supplementary material Fig.…”
Section: Research Articlementioning
confidence: 99%